Evaluation of Socio-economic Impacts of Incidents on the Railway Infrastructure - Hromádka, Vít; Korytárová, Jana; Vítková, Eva; Funk, Tomáš; Seelmann, Herbert (Scipedia, 2020)
Evaluation of the economic efficiency of investment projects in transport infrastructure in the Czech Republic is methodically based on the Departmental Methodology of the Ministry of Transport. Economic cash flows, generated in accordance with the CBA principles, are modelled within this methodology on the basis of the evaluation of socio-economic impact of individual projects. In the case of the railway infrastructure constructions, the socio-economic impacts used by the methodology do not include benefits associated with increasing safety and reliability of the railway infrastructure network due to new security systems implementation. Determination of socio-economic impacts associated with specific types of incidents on the railway which are caused by insufficient railway infrastructure security and which could be eliminated by the implementation of the higher-level signaling equipment forms the subject of the research. The research is based on the analysis of a database of incidents occurring on the railway in the Czech Republic in the 2009– 2018 period, which describes the basic impacts associated with a particular incident. Statistical data on the railway infrastructure is also used to determine the impact of incidents in addition to the database. The key outcomes of the research are the determination of methodological steps for the evaluation of the impacts of incidents on the railway and a case study for their verification. Future research will focus on making evaluation of the above-mentioned benefits more detailed. Research outcomes will improve decision-making process on selection and financing of the projects related to railway infrastructure safety for their future implementation.

Evaluation of the economic efficiency of investment projects in transport infrastructure in the Czech Republic is methodically based on the Departmental Methodology of the Ministry of Transport. Economic cash flows, generated in accordance with the CBA principles, are modelled within this methodology on the basis of the evaluation of socio-economic impact of individual projects. In the case of the railway infrastructure constructions, the socio-economic impacts used by the methodology do not include benefits associated with increasing safety and reliability of the railway infrastructure network due to new security systems implementation. Determination of socio-economic impacts associated with specific types of incidents on the railway which are caused by insufficient railway infrastructure security and which could be eliminated by the implementation of the higher-level signaling equipment forms the subject of the research. The research is based on the analysis of a database of incidents occurring on the railway in the Czech Republic in the 2009– 2018 period, which describes the basic impacts associated with a particular incident. Statistical data on the railway infrastructure is also used to determine the impact of incidents in addition to the database. The key outcomes of the research are the determination of methodological steps for the evaluation of the impacts of incidents on the railway and a case study for their verification. Future research will focus on making evaluation of the above-mentioned benefits more detailed. Research outcomes will improve decision-making process on selection and financing of the projects related to railway infrastructure safety for their future implementation.
Evaluation of Socio-economic Impacts of Incidents on the Railway Infrastructure
Keywords: Socio-Economic Impacts; Investment Project; Railways; Incidents; Evaluation; Socio-Economic Impacts; Investment Project; Railways; Incidents; Evaluation